A niobium-titanium alloy ultrafine wire for high vacuum suction and its preparation method and application

By using niobium titanium alloy ultrafine filament material, combined with magnetic levitation smelting, high temperature forging, cold drawing process and microarc oxidation technology, the mechanical strength difference and high cost of existing getter materials when used in high-vacuum electric vacuum devices are solved. The problem is that high-efficiency and low-cost high vacuum suction performance is achieved.

CN118497581BActive Publication Date: 2025-02-25杭州浩忆科技有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410626902.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-21
Publication Date
2025-02-25
Estimated Expiration
2044-05-21

AI Technical Summary

Technical Problem

When used in high-vacuum electrical vacuum devices, existing non-evaporative getter materials have problems such as poor mechanical strength, high activation temperature, complex production process and high cost, which limit their use in specific use environments.

Method used

The ultrafine filament of niobium titanium alloy is prepared through magnetic levitation smelting, high-temperature forging, cold drawing and other processes, and combined with microarc oxidation technology to prepare porous and rough structures on the surface of the filament to form an efficient and low-cost high-vacuum getter material.

Benefits of technology

It achieves high vacuum suction performance, reduces raw material costs, simplifies process flow, and improves the mechanical properties and suction efficiency of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118497581B_ABST
    Figure CN118497581B_ABST
Patent Text Reader

Abstract

The invention discloses a niobium-titanium alloy ultrafine wire for high vacuum suction and a preparation method and application thereof. Sponge titanium, niobium sheets and titanium-niobium master alloy are uniformly mixed to prepare an alloy ingot; the alloy ingot is subjected to a homogenization treatment to eliminate component segregation; the alloy ingot is subjected to a blanking forging treatment, and the diameter of the rod blank after the forging treatment is 50-60 mm; the rod blank is subjected to high-temperature rolling until a rod blank with a diameter of less than 6 mm is obtained; a hot drawing process is performed until a rod blank with a diameter of less than 1 mm is obtained; a cold drawing process is performed, and intermediate annealing is performed when the deformation reaches 40%-50%, and the annealing temperature is 600-700°C until a rod blank with a diameter of less than 0.3 mm is obtained; surface pickling is performed to remove oxide scale, and then ultrasonic cleaning and drying treatment are performed to form a disk to prepare the niobium-titanium alloy ultrafine wire. The present invention adopts magnetic levitation melting, high temperature forging, cold drawing and other process designs to prepare niobium-titanium binary alloy ultrafine wire (diameter ≤ 0.3mm), and prepares a porous rough structure on the surface of the wire through micro-arc oxidation technology. When used as a high vacuum suction device, it has the performance advantages of high efficiency and low cost and has huge market value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of getter materials, and in particular to an ultrafine niobium-titanium alloy wire for high vacuum gettering, and a preparation method and application thereof. Background Art

[0002] In order to maintain or improve the vacuum degree inside the electric vacuum device, a getter material is usually set inside the device to absorb the residual gas inside the vacuum device and the gas continuously released by the components during storage, so as to maintain the performance of the device for a long time and significantly extend its life. With the rapid development of vacuum technology and electronic technology, electric vacuum devices have put forward higher requirements for vacuum conditions, life and stability. The residual gas after the electric vacuum device is exhausted and sealed, the active gas released by the device during operation, and the gas such as H2 that penetrates through the device shell will seriously affect the vacuum degree of the electric vacuum device. The getter material can absorb the active gas in the electric vacuum device, provide the vacuum degree required after the device is sealed, and can maintain the vacuum degree for a long time to ensure the life, stability and reliability of the device. Therefore, the research and development of getter materials directly affects the performance of electric vacuum devices.

[0003] The getter materials developed in the existing field can be divided into two categories: evaporative getter materials and non-evaporative getter materials. Evaporative getter materials absorb air by forming a film after heating and evaporation, while non-evaporative getter materials do not change their shape after activation and can form stable compounds with active gases at room temperature for absorption. However, evaporative getter materials will bring evaporated metal atoms when working, causing inter-electrode leakage and other factors that affect the normal operation of vacuum devices, narrowing their application range. Non-evaporative getter materials do not need to evaporate the getter metal, will not pollute the device, and have the characteristics of small size and high pumping speed, so they are widely used in the field of vacuum devices. Traditional non-evaporable getter materials have mainly formed three categories in the development process: pressed type, porous sintered type and thin film type. The pressed non-evaporable getter materials mainly include Zr-Al and Zr-V-Fe alloys, the porous sintered non-evaporable getter materials mainly include Zr-C, Zr-ZrVFe and Ti-Mo alloys, and the thin film non-evaporable getter materials mainly include TiZrV alloy thin films. By comparing the performances of the above three existing non-evaporable getter materials, it can be found that: the pressed non-evaporable getter materials have poor mechanical strength; although the porous sintered non-evaporable getter materials have high mechanical strength, the activation temperature is high and the manufacturing process is complex; the thin film non-evaporable getter materials are limited by the getter capacity and their own size and shape, and are generally limited to use in tiny electric vacuum devices. These problems existing in current applications limit the use of non-evaporable getter materials in specific use environments.

[0004] It is known that some transition metals such as titanium, zirconium, hafnium, etc. can form an active surface with high adsorption capacity when activated, have excellent gettering performance, and can react chemically with almost all gases except inert gases. At the same time, the gettering performance of gettering materials mainly depends on the surface adsorption capacity, and higher requirements are placed on the adsorption surface area of ​​the alloy. Studies have found that the larger the specific surface area, the larger the effective interaction area between the material and the active gas molecules, and the higher the adsorption probability. Therefore, the use of transition metals to prepare new adsorption alloy materials that have high adsorption characteristics, excellent mechanical properties, and large specific surface area has great application potential. Researchers have tried to prepare some titanium alloy wires by adding alloying elements such as Mo, Ta, and Nb, which have been used in some high vacuum devices due to their high gettering performance, large specific surface area, and good welding ability.

[0005] In the 1970s, China first began to develop Ti-15Ta alloy wire as a getter material in high vacuum devices, and successfully realized the use of this alloy wire. Studies have found that once the titanium-tantalum wire is heated and degassed, it has the ability to getter air itself and can be used as a non-evaporable getter. During the activation process, a titanium film layer of a certain thickness is pre-formed on the surface of the alloy wire, and its gettering effect is better. The method of lowering the substrate temperature during the formation of the titanium film layer and appropriately increasing the working temperature after the titanium film is formed for a certain period of time can maximize the vacuum degree of the system. However, further research has found that with the appropriate increase in the number of activation times of the titanium-tantalum wire, the titanium-tantalum wire's own degassing gradually decreases, the titanium film thickness increases, and the system vacuum degree gradually increases.

[0006] Current development and application of niobium-free titanium binary alloy ultrafine wires in the field of high vacuum getter devices in China. Summary of the invention

[0007] The purpose of the present invention is to provide a niobium-titanium alloy ultrafine wire for high vacuum aspiration and a preparation method and application thereof, so as to overcome the deficiencies in the prior art.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] The present application discloses a method for preparing a niobium-titanium alloy ultrafine wire for high vacuum suction, comprising the following steps:

[0010] S1, uniformly mixing titanium sponge, niobium sheet and titanium-niobium master alloy to prepare an alloy ingot;

[0011] S2, homogenizing the alloy ingot obtained in step S1 at 1100° C. to 1300° C. for 6 to 10 hours to eliminate component segregation;

[0012] S3, performing a blanking forging process on the alloy ingot after the homogenization treatment in step S2, wherein the diameter of the forged billet is 50-60 mm; then performing high temperature rolling on the billet, wherein the deformation amount of each rolling process is 15%-20%; until a billet with a diameter of less than 6 mm is obtained, the high temperature rolling is completed;

[0013] S4, performing a hot drawing process on the bar blank that has completed high temperature rolling in step S3, with a drawing deformation of 10% to 15% per pass, until a bar blank with a diameter of less than 1 mm is obtained, completing the hot drawing process;

[0014] S5, cold drawing the rod blank after hot drawing in step S4, with the deformation of each cold drawing being 5%-10%, and intermediate annealing being performed when the deformation reaches 40%-50%, with the annealing temperature being 600-700°C; until a rod blank with a diameter of less than 0.3 mm is obtained, and the cold drawing process is completed;

[0015] S6, pickling the surface of the rod blank after the cold drawing process in step S5 to remove the oxide scale, and then ultrasonically cleaning and drying it to form a coil to produce niobium-titanium alloy ultrafine wire.

[0016] Preferably, step S1 specifically includes the following operations: uniformly mixing titanium sponge, niobium sheet and titanium-niobium master alloy, and performing suspension smelting for at least two times; welding electrodes obtained by suspension smelting to form a consumable electrode, and then performing consumable electrode arc melting for at least three times to prepare an alloy ingot.

[0017] Preferably, the blank forging temperature in step S3 is 1100°C to 1200°C; the high temperature rolling annealing temperature is 900°C to 1000°C.

[0018] Preferably, the annealing temperature of the hot drawing in step S4 is 900-1000°C, and the vacuum degree is 10 -3 Below Pa.

[0019] The present invention discloses a niobium-titanium alloy ultrafine wire for high vacuum aspiration, which is prepared by adopting the above-mentioned method for preparing a niobium-titanium alloy ultrafine wire for high vacuum aspiration; each component consists of 40% to 60% niobium and the remainder titanium according to atomic percentage.

[0020] The present invention also discloses an application of a niobium-titanium alloy ultrafine wire for high vacuum suction as a high vacuum suction device. A1, the niobium-titanium alloy ultrafine wire is cut into 50-100 mm size segments, the two ends are clamped and placed in an electrolyte, and a micro-arc oxidation treatment is applied in a constant voltage mode; A2, the oxidized product is ultrasonically cleaned, and a high vacuum suction device product is obtained after drying. The surface morphology and size are observed by a scanning electron microscope, and the wire is welded with a Kovar alloy used for an airtight sealing device and then powered on to test the suction performance of the device.

[0021] Preferably, the electrolyte composition is alkali metal borate and hydroxyapatite, the alkali metal borate concentration is 0.1~0.3 mol / L, and the hydroxyapatite concentration is 3~15 g / L; the positive voltage is controlled to be 200~600 V, the negative voltage is 0~30 V, the current frequency is 300~600 Hz, the duty cycle is 9%~15%, the oxidation reaction time is 5~20 min, and the reaction temperature is controlled below 50°C.

[0022] Beneficial effects of the present invention:

[0023] The present invention adopts magnetic levitation melting, high temperature forging, cold drawing and other process designs to prepare niobium-titanium binary alloy ultrafine wire (diameter ≤ 0.3mm), and uses micro-arc oxidation technology to prepare a porous rough structure on the surface of the wire. When used as a high vacuum getter device, it has the performance advantages of high efficiency and low cost, and has great market value;

[0024] Compared with the titanium-tantalum alloy wire developed domestically, the niobium-titanium binary alloy ultrafine wire has two main advantages as a high vacuum getter material: (1) The melting point of the Nb element is lower than that of the Ta element. Adding the Nb element through an intermediate alloy during smelting can significantly reduce the smelting difficulty and improve the uniformity of the raw materials; (2) The market price of the Nb element is lower than that of the Ta element. The application and promotion of this alloy can effectively reduce the cost of the getter alloy wire.

[0025] The features and advantages of the present invention will be described in detail through embodiments in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a schematic diagram of the surface morphology of niobium-titanium alloy ultrafine wire observed by scanning electron microscope;

[0027] Figure 2 This is a schematic diagram of testing the air absorption performance of the device after welding the Kovar alloy used in the airtight sealing device in Example 4 and applying power.

[0028] Figure 3 This is a schematic diagram of niobium segregation distribution observed by backscattering scanning electron microscope in comparative example 1. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below through the accompanying drawings and embodiments. However, it should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.

[0030] The embodiment of the present invention provides a method for preparing an ultrafine niobium-titanium alloy wire for high vacuum gettering, comprising the following steps:

[0031] S1, uniformly mixing titanium sponge, niobium sheet and titanium-niobium master alloy to prepare an alloy ingot;

[0032] Specifically, titanium sponge, niobium sheets and titanium-niobium master alloy are uniformly mixed and subjected to suspension smelting. After all raw materials are melted, the smelting times are required to be no less than two times to ensure the uniformity of the composition and avoid inclusions and segregation in the ingot. The electrodes obtained by the suspension smelting are welded and combined as consumable electrodes. To ensure the uniformity of the composition of the molten pool, the consumable electrode arc melting is further completed no less than three times to prepare the alloy ingot.

[0033] S2. The alloy ingot is homogenized at 1100℃~1300℃ for 6~10 hours to eliminate component segregation;

[0034] S3. Niobium-titanium alloy has a high melting point. In order to ensure that the internal grains are fully heated and deformable, the forging temperature of the ingot is set to 1100℃-1200℃, the diameter of the bar after forging is set to 50-60mm, and the annealing temperature of high-temperature rolling is 900-1000℃; Niobium-titanium alloy has good processing and forming performance, and at the same time, to avoid excessive deformation causing cracking on the surface of the hot-rolled bar, the deformation of each rolling pass is set to 15%-20%.

[0035] S4. In order to meet the specifications of conventional processing equipment, small-sized niobium-titanium alloy bars need to be prepared by drawing process. The hot drawing process is required when the bar billet is rolled to a diameter of less than 6mm. The hot drawing annealing temperature is set to 900-1000℃, and the vacuum degree in the annealing environment is controlled below 10-3Pa to avoid excessive oxidation and cracking of the surface. In order to avoid surface cracking, the deformation of each drawing process is required to be 10%-15%;

[0036] S5. To improve the mechanical properties and surface quality of niobium-titanium alloy ultrafine wire, it is required to carry out cold drawing process when the wire is drawn to a diameter of less than 1mm. To avoid wire breakage, the deformation of each cold drawing process is set to 5%-10%. To eliminate the work hardening inside the wire after multiple drawing, an intermediate annealing process is carried out when the deformation reaches 40%-50%, and the annealing temperature is set to 600-700℃.

[0037] S6. The rod blank that has completed the cold drawing process in step S5 is pickled on the surface to remove the oxide scale, and then ultrasonically cleaned and dried before being coiled to form a niobium-titanium alloy ultrafine wire; each component is composed of 40% to 60% niobium and the remainder titanium according to atomic percentage.

[0038] The above-mentioned niobium-titanium alloy ultrafine wire is subjected to surface micro-arc oxidation treatment to provide its application as a high vacuum getter device. The specific preparation process includes:

[0039] A1. Cut the niobium-titanium alloy ultrafine wire into 50-100mm segments, clamp the two ends and place them in the electrolyte, and control the constant voltage mode to apply micro-arc oxidation treatment; A2. Ultrasonic cleaning is performed on the oxidized product, and a high vacuum aspiration device product is obtained after drying. The surface morphology and size are observed by scanning electron microscopy, and the device is welded with the Kovar alloy used for the airtight sealing device and then powered on to test the aspiration performance of the device.

[0040] The electrolyte comprises alkali metal borate and hydroxyapatite, the concentration of the alkali metal borate is 0.1-0.3 mol / L, and the concentration of the hydroxyapatite is 3-15 g / L; the positive voltage is controlled to be 200-600 V, the negative voltage is 0-30 V, the current frequency is 300-600 Hz, the duty cycle is 9%-15%, the oxidation reaction time is 5-20 min, and the reaction temperature is controlled below 50°C.

[0041] Embodiment 1:

[0042] 1) High-purity titanium sponge, high-purity niobium sheet and high-purity titanium-niobium master alloy (purity greater than 99.99%) are uniformly mixed as raw materials, and suspension smelting is first performed twice; the electrodes obtained by suspension smelting are welded and combined as consumable electrodes, and three consumable electrode arc meltings are completed to prepare alloy ingots;

[0043] 2) The alloy ingot is homogenized in a vacuum heat treatment furnace at 1100°C for more than 10 hours to further eliminate component segregation;

[0044] 3) The alloy ingot is subjected to open forging treatment, the open forging temperature is 1100°C, the diameter of the forged bar is 60mm, the annealing temperature of high temperature rolling is 900°C, and the deformation of each rolling pass is 15%;

[0045] 4) When the rod is rolled to a diameter of less than 6 mm, a hot drawing process is performed. The hot drawing annealing temperature is 900°C and the vacuum degree in the annealing environment is controlled at 10 -3 Pa to avoid excessive surface oxidation and cracking, the drawing deformation per pass is 10%;

[0046] 5) When the wire is hot drawn to a diameter of less than 1 mm, a cold drawing process is performed. The deformation of each cold drawing process is 5%. When the deformation reaches 40%, intermediate annealing is performed at a temperature of 600 ° C.

[0047] 6) When the wire is cold drawn to a diameter of less than 0.3 mm, the surface is pickled to remove the oxide scale, and then ultrasonically cleaned and dried before being coiled to form niobium-titanium alloy ultrafine wire.

[0048] Embodiment 2:

[0049] 1) High-purity titanium sponge, high-purity niobium sheet and high-purity titanium-niobium master alloy (purity greater than 99.99%) are uniformly mixed as raw materials, and suspension smelting is first performed for three times; the electrodes obtained by suspension smelting are welded and combined as consumable electrodes, and four times of consumable electrode arc melting are completed to prepare alloy ingots;

[0050] 2) The alloy ingot is homogenized in a vacuum heat treatment furnace at 1200°C for more than 8 hours to further eliminate component segregation;

[0051] 3) The alloy ingot is subjected to open forging treatment, the open forging temperature is 1150°C, the diameter of the forged bar is 55mm, the annealing temperature of high temperature rolling is 950°C, and the deformation of each rolling pass is 18%;

[0052] 4) When the rod is rolled to a diameter of less than 6 mm, a hot drawing process is performed. The hot drawing annealing temperature is 950°C and the vacuum degree in the annealing environment is controlled at 10 -3 Pa or less to avoid excessive surface oxidation and cracking, and the drawing deformation per pass is 13%;

[0053] 5) After the wire is hot drawn to a diameter of less than 1 mm, a cold drawing process is performed. The deformation of each cold drawing process is 8%. When the deformation reaches 45%, intermediate annealing is performed at a temperature of 650°C.

[0054] 6) When the wire is cold drawn to a diameter of less than 0.3 mm, the surface is pickled to remove the oxide scale, and then ultrasonically cleaned and dried before being coiled to form niobium-titanium alloy ultrafine wire.

[0055] Embodiment 3:

[0056] 1) High-purity titanium sponge, high-purity niobium sheet and high-purity titanium-niobium master alloy (purity greater than 99.99%) are uniformly mixed as raw materials, and suspension smelting is first performed for three times; the electrodes obtained by suspension smelting are welded and combined as consumable electrodes, and four times of consumable electrode arc melting are completed to prepare alloy ingots;

[0057] 2) The alloy ingot is homogenized in a vacuum heat treatment furnace at 1300°C for more than 6 hours to further eliminate component segregation;

[0058] 3) The alloy ingot is subjected to open forging treatment, the open forging temperature is 1200°C, the diameter of the forged bar is 60mm, the annealing temperature of high temperature rolling is 1000°C, and the deformation of each rolling pass is 20%;

[0059] 4) When the rod is rolled to a diameter of less than 6 mm, a hot drawing process is performed. The hot drawing annealing temperature is 1000°C, and the vacuum degree in the annealing environment is controlled at 10 -3Pa or less to avoid excessive oxidation and cracking of the surface, and the deformation of each drawing pass is 15%;

[0060] 5) When the wire is hot drawn to a diameter of less than 1 mm, a cold drawing process is performed. The deformation of each cold drawing process is 10%. When the deformation reaches 50%, intermediate annealing is performed at a temperature of 700 ° C.

[0061] 6) When the wire is cold drawn to a diameter of less than 0.3 mm, the surface is pickled to remove the oxide scale, and then ultrasonically cleaned and dried before being coiled to form niobium-titanium alloy ultrafine wire.

[0062] application:

[0063] 1) The niobium-titanium alloy ultrafine wire of Example 2 is cut into 40-size segments, the two ends of the wire are clamped by a tool and placed in an electrolyte, and a micro-arc oxidation treatment is applied under a constant voltage mode;

[0064] 2) The oxidized product is ultrasonically cleaned and dried to obtain a high vacuum aspirator device product. The surface morphology and size are observed by scanning electron microscopy, such as Figure 1 As shown in the figure, the Kovar alloy used for the hermetic sealing device is welded and then powered on to test the gas absorption performance of the device. Figure 2 shown.

[0065] The electrolyte composition is alkali metal borate and hydroxyapatite, the alkali metal borate concentration is 0.2 mol / L, and the hydroxyapatite concentration is 8 g / L. The positive voltage is controlled to be 400 V, the negative voltage is 15 V, the current frequency is 450 Hz, the duty cycle is 12%, the oxidation reaction time is 12 min, and the reaction temperature is controlled at 40°C.

[0066] Comparative Example 1:

[0067] 1) High-purity titanium sponge, high-purity niobium sheet and high-purity titanium-niobium master alloy (purity greater than 99.99%) are uniformly mixed, electrodes are pressed and welded together as consumable electrodes, and three consumable electrode arc meltings are completed to prepare alloy ingots;

[0068] 2) The alloy ingot was homogenized in a vacuum heat treatment furnace at 1100°C for more than 10 hours in an attempt to eliminate component segregation. Samples were cut and observed to find that the enrichment of niobium was still present.

[0069] 3) The alloy ingot is subjected to open forging treatment, the open forging temperature is 1100°C, the diameter of the forged bar is 60mm, the annealing temperature of high temperature rolling is 900°C, and the deformation of each rolling pass is 15%;

[0070] 4) When the rod is rolled to a diameter of less than 6 mm, a hot drawing process is performed. The hot drawing annealing temperature is 900°C and the vacuum degree in the annealing environment is controlled at 10 -3 Pa to avoid excessive surface oxidation and cracking, the drawing deformation per pass is 10%;

[0071] 5) After the wire is hot-drawn to a diameter of less than 1 mm, a cold drawing process is performed. The deformation of each cold drawing is 5%. When the deformation reaches 40%, intermediate annealing is performed at 600°C. Due to the enrichment of components inside the alloy and the inclusion of niobium, the ultrafine wire is prone to internal defects and breakage during preparation, resulting in a significant decrease in the processing performance of the wire.

[0072] 6) When the wire is cold drawn to a diameter of less than 0.3 mm, the surface is pickled to remove the oxide scale, and then ultrasonically cleaned and dried before being coiled to form niobium-titanium alloy ultrafine wire.

[0073] Compared with Example 1, this comparative example only used consumable electrode smelting in the smelting process. Since the melting points of niobium and titanium are quite different (800°C), it is impossible to achieve uniform flow of alloy components in the molten pool only through consumable smelting. The riser was cut to observe the composition and scanning electron microscope backscattering. It was found that Figure 3 As shown, there is local enrichment and segregation of niobium in the ingot. The distribution of niobium segregation in the riser observed by scanning electron microscopy is shown as the white bright spot in the figure below;

[0074] Comparative Example 2:

[0075] 1) High-purity titanium sponge, high-purity niobium sheet and high-purity titanium-niobium master alloy (purity greater than 99.99%) are uniformly mixed as raw materials, and suspension smelting is first performed for three times; the electrodes obtained by suspension smelting are welded and combined as consumable electrodes, and four times of consumable electrode arc melting are completed to prepare alloy ingots;

[0076] 2) The alloy ingot is homogenized in a vacuum heat treatment furnace at 1200°C for more than 8 hours to further eliminate component segregation;

[0077] 3) The alloy ingot is subjected to open forging treatment, the open forging temperature is 1150°C, the diameter of the forged bar is 55mm, the annealing temperature of high temperature rolling is 950°C, and the deformation of each rolling pass is 18%;

[0078] 4) When the rod is rolled to a diameter of less than 6 mm, a hot drawing process is performed. The hot drawing annealing temperature is 950°C and the vacuum degree in the annealing environment is controlled at 10 -3 Pa or less to avoid excessive surface oxidation and cracking, and the drawing deformation per pass is 20%;

[0079] 5) After the wire is hot drawn to a diameter of less than 1 mm, a cold drawing process is performed. The deformation of each cold drawing process is 8%. When the deformation reaches 45%, intermediate annealing is performed at a temperature of 650°C.

[0080] 6) When the wire is cold drawn to a diameter of less than 0.3 mm, the surface is pickled to remove the oxide scale, and then ultrasonically cleaned and dried before being coiled to form niobium-titanium alloy ultrafine wire.

[0081] Compared with Example 2, the single-pass deformation amount in the hot drawing process of this comparative example reached 20%. Due to the limited processing deformation capacity of niobium-titanium alloy, the excessive deformation amount during the hot drawing process caused the deformation of the internal grains of the alloy to be hindered and microcracks to appear. After diffusing to the surface of the wire, microcracks occurred during the hot drawing. In addition, the internal stress introduced by the large deformation amount caused the diameter of the deformed wire to be inconsistent with expectations.

[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing ultrafine niobium-titanium alloy wire for high vacuum suction, characterized in that: The steps include: S1, uniformly mixing titanium sponge, niobium sheet and titanium-niobium master alloy to prepare an alloy ingot; Step S1 specifically includes the following operations: uniformly mixing titanium sponge, niobium sheet and titanium-niobium master alloy, and performing suspension smelting for at least two times; welding electrodes obtained by suspension smelting to form a consumable electrode, and then performing consumable electrode arc smelting for at least three times to prepare an alloy ingot; S2, homogenizing the alloy ingot obtained in step S1 at 1100° C. to 1300° C. for 6 to 10 hours to eliminate component segregation; S3, performing a blanking forging process on the alloy ingot after the homogenization treatment in step S2, wherein the diameter of the forged billet is 50-60 mm; then performing high temperature rolling on the billet, wherein the deformation amount of each rolling process is 15%-20%; until a billet with a diameter of less than 6 mm is obtained, the high temperature rolling is completed; The blank forging temperature in step S3 is 1100°C to 1200°C; the annealing temperature of high temperature rolling is 900°C to 1000°C; S4, performing a hot drawing process on the bar blank that has completed high temperature rolling in step S3, with a drawing deformation of 10% to 15% per pass, until a bar blank with a diameter of less than 1 mm is obtained, completing the hot drawing process; The annealing temperature of the hot drawing in step S4 is 900-1000°C, and the vacuum degree is below 10-3Pa; S5, cold drawing the rod blank after hot drawing in step S4, with the deformation of each cold drawing being 5%-10%, and intermediate annealing being performed when the deformation reaches 40%-50%, with the annealing temperature being 600-700°C; until a rod blank with a diameter of less than 0.3 mm is obtained, and the cold drawing process is completed; S6, pickling the surface of the rod blank after the cold drawing process in step S5 to remove the oxide scale, and then ultrasonically cleaning and drying it to make a niobium-titanium alloy ultrafine wire; the niobium-titanium alloy ultrafine wire for high vacuum suction consists of 40% to 60% niobium and the remainder titanium according to atomic percentage; The application of the high vacuum gettering niobium titanium alloy ultrafine wire as a high vacuum gettering device is as follows: A1. Cut the niobium-titanium alloy ultrafine wire into 50-100 mm segments, clamp both ends and place them in the electrolyte, and control the constant voltage mode to apply micro-arc oxidation treatment; A2. The oxidized product is ultrasonically cleaned and dried to obtain a high vacuum aspirator device product. The surface morphology and size are observed using a scanning electron microscope. After welding with the Kovar alloy used for the airtight sealing device, power is applied to test the aspirator performance of the device.

2. The use of the ultrafine niobium-titanium alloy wire for high vacuum gettering as claimed in claim 1 as a high vacuum gettering device, characterized in that: A1. Cut the niobium-titanium alloy ultrafine wire into 50-100 mm segments, clamp both ends and place them in the electrolyte, and control the constant voltage mode to apply micro-arc oxidation treatment; A2. The oxidized product is ultrasonically cleaned and dried to obtain a high vacuum aspirator device product. The surface morphology and size are observed using a scanning electron microscope. After welding with the Kovar alloy used for the airtight sealing device, power is applied to test the aspirator performance of the device.

3. The use of the ultrafine niobium-titanium alloy wire for high vacuum gettering as claimed in claim 2 as a high vacuum gettering device, characterized in that: The electrolyte comprises alkali metal borate and hydroxyapatite, the concentration of alkali metal borate is 0.1-0.3 mol / L, and the concentration of hydroxyapatite is 3-15 g / L; the positive voltage is controlled to be 200-600 V, the negative voltage is 0-30 V, the current frequency is 300-600 Hz, the duty cycle is 9%-15%, the oxidation reaction time is 5-20 min, and the reaction temperature is controlled below 50°C.

Citation Information

Patent Citations

  • Preparation method of Ti-6Al-4V alloy welding wire suitable for repair welding of titanium alloy casting

    CN106041369A

  • Processing method of Ti45Nb titanium alloy straight wire

    CN117483473A

  • Surface bioactive coating prepared by micro-arc oxidation of titanium-zirconium alloy for implant and preparation method of surface bioactive coating

    CN117904691A